(3GdjJjes - (3TGfGb GdgfOjs
(3ChdgG (B:s
(3hgh ef CSQGQ MceGA GdgfO hcGfJ Gdedhc JUhf gPG GdcJGH ai NRGfJge Yf ChdGOge s
(3BNQgG (B:s
(3jfHZi Cf jSbW ef gPG GdcJGH fYJ GdLGQjI GdeSeheI dCf gfG aYd GdLGgdjI ef GdgfO Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1425s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs